2000
DOI: 10.1046/j.1471-4159.2000.0751368.x
|View full text |Cite
|
Sign up to set email alerts
|

Functional Characterization of a cis‐Acting DNA Antisilencer Region that Modulates Myelin Proteolipid Protein Gene Expression

Abstract: Regulation of myelin proteolipid protein (Plp) gene expression is tightly controlled, both spatially and temporally. Previously, we have shown with transgenic mice that a Plp-lacZ fusion gene (which includes the entire sequence for Plp intron 1 DNA) is regulated in a similar manner to endogenous Plp gene expression. Furthermore, by deletion-transfection analyses using assorted Plp-lacZ constructs with partial deletion of Plp intron 1 sequences, we have shown that the first intron possesses an antisilencer regi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
48
0

Year Published

2004
2004
2011
2011

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 15 publications
(50 citation statements)
references
References 26 publications
2
48
0
Order By: Relevance
“…The transgene contains Plp genomic DNA extending from the proximal 2.4 kb of 5′-flanking DNA, downstream to the first 37 bp of exon 2, which were used to drive expression of a lacZ reporter gene cassette. Thus the transgene contains the Plp promoter as well as a tissue-specific enhancer located in Plp intron 1 DNA [24,25]. Expression of the PLP(+)Z transgene was evaluated in affected Plp jp males, which express a mutated Plp gene (Plp jp ), and compared to that produced in wild-type male littermates containing the normal Plp gene.…”
Section: Plp(+)z Transgene Expression In the Developing Cns In Plp Jpmentioning
confidence: 99%
“…The transgene contains Plp genomic DNA extending from the proximal 2.4 kb of 5′-flanking DNA, downstream to the first 37 bp of exon 2, which were used to drive expression of a lacZ reporter gene cassette. Thus the transgene contains the Plp promoter as well as a tissue-specific enhancer located in Plp intron 1 DNA [24,25]. Expression of the PLP(+)Z transgene was evaluated in affected Plp jp males, which express a mutated Plp gene (Plp jp ), and compared to that produced in wild-type male littermates containing the normal Plp gene.…”
Section: Plp(+)z Transgene Expression In the Developing Cns In Plp Jpmentioning
confidence: 99%
“…Originally this positive regulatory element was classified as an antisilencer since it seemed to override repression mediated by multiple negative elements located elsewhere within intron 1 DNA [76]. However, subsequent experiments showed that the positive regulatory element possessed enhancer-like properties; i. e. it functioned in an orientation-independent manner and multiple copies of the element resulted in higher levels of reporter gene expression in transfected N20.1 cells [109]. The positive regulatory element, probably better characterized as a region, is contained within mouse intron 1 DNA positions 1083 -1777 (based on consecutively numbering the intron sequence with the first bp designated as 1).…”
Section: Temporal Regulation Of Plp Gene Expressionmentioning
confidence: 99%
“…This was the only positive regulatory element to be mapped in the intron by deletiontransfection analysis. A plethora of putative transcription factor binding sites within this sequence has been noted [109]. Multiple factors appear bind to this region [76,109], possibly forming an enhanceosome.…”
Section: Temporal Regulation Of Plp Gene Expressionmentioning
confidence: 99%
See 1 more Smart Citation
“…Transfection analysis using a battery of Plp1-lacZ constructs containing partial deletion of Plp1 intron 1 DNA revealed the presence of a single positive-regulatory element within the intron that is active in N20.1 cells (Dobretsova and Wight, 1999). Besides being able to overcome (or counterbalance) the effects from negative-regulatory elements located elsewhere in the intron, the positive-regulatory element functions as an enhancer in N20.1 cells (Dobretsova et al, 2000; Meng et al, 2005). Thus, we designated the positive regulatory element ASE ( a nti- s ilencer/ e nhancer).…”
Section: Introductionmentioning
confidence: 99%